A Mari Prophecy and Nathan's Dynastic Oracle - Malamat, A. (Fs Fohrer)
A. 1121, published by G. Dossin apud A. Lods in H. H. Rowley (Ed.), Studies in Old Testament Prophecy Presented to T. H. Robinson (1950) 103-107.